Implementasi Sistem Rekomendasi Rute Penanganan Gangguan Berbasis Android menggunakan Best First Search - Nurdin, Abdul Muhamin; Nusyura, Fauzan; Rahmanti, Farah Zakiyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The field of information and communication technology essentially has increased development along with increasing access to information which alternates with the internet network which allows computers to be connected to each other. An internet provider is an organization that provides internet access services to its customers. Customer satisfaction with internet services is crucial, so handling internet disruption reports is also a primary focus. The process of following up on internet disruption complaints sometimes requires a long time because there is no recommended route to be resolved by technicians. Therefore, this research aims to provide a solution for recommending the shortest route using the Best First Search method based on Android. The result of this research is a mobile application for technicians to resolve visited disruption points based on the shortest route.